Time is of the Essence: Impact of a More Aggressive Chemical Venous Thromboembolism Prophylaxis Regimen on Trauma Patients. Issue 3 (March 2022) - Schroeppel, Thomas J.; Clement, Lesley P.; Douville, Alyssa A.; Schmoekel, Nathan H.; Stassinopoulos, Jerry; Decker, Cassandra; Stillman, Zachery E.; Rodriquez, Jennifer; Brockman, Valerie P.; Hennessy, Elizabeth; Heise, Holly; Khan, Abid D.
Background: Trauma patients are at high risk for venous thromboembolism (VTE). Opportunity for chemical VTE prophylaxis improvement was identified and practice was altered to start chemoprophylaxis on admission in most patients. The purpose of this study was to determine if early VTE prophylaxis is safe and reduces VTE. Methods: The trauma registry was queried over a 12-month period for patients admitted greater than 1 day for traumatic injury. The study spanned 6 months on either side of instituting aggressive chemoprophylaxis. Patients were risk adjusted on demographics, Injury Severity Score, transfusions, procedure type, length of stay, and mortality. Pre-intervention patients were then compared to patients in the aggressive cohort with the primary outcome of VTE. Secondary outcomes included transfusions, mortality, and length of stay (LOS). Results: 1597 patients were identified over the study period with 754 (47%) patients in the aggressive period. There were no differences in age, sex, Injury Severity Score, transfusions, procedures, or LOS between cohorts. Pre-algorithm patients were more likely to have penetrating mechanism (9.3% vs 6.6%; P = .009) and longer time to VTE prophylaxis (23.3 vs 13.9 hours; P < .001). No differences were noted in anticoagulant, VTE rate (2.0% vs 1.2%; P = .195), or mortality. Linear regression analysis identified time to chemical prophylaxis as significant predictor of VTE (β = 43.9, P < .001). Conclusions: Early aggressive chemical VTE prophylaxis is safe without increasing transfusions. Venous thromboembolism rates were decreased, but did not reach statistical significance.